Bats of Bako National Park, Sarawak, Malaysian Borneo - Jayaraj V.K; M.T. Abdullah; Faisal A.A. Khan; Besar Ketol (2007)
Two separate assessments on bats diversity were conducted in Bako National Park for 12 trapping-nights. Our first assessment was conducted from 8th to 12th February 2005 followed by the second assessment from 28th August to 3rd September 2005. A total of 295 individuals from 22 species of bats were captured using mist-nets and harp traps during the survey,which accumulated to 226 trapping-nights. Hipposideros vervinus was recorded as the most abundance species with 30.85% of total captures. A total of eight new records of bats have been added to this park : Emballonura monticola, Rhinolophus luctus, Hipposiders ater,Hipposideros bicolor,Myotis muricola, Myotis ater,Pipistrellus vondermanni and Kerivoula pellucida. With these additional records,there are now at least 34 species of bats known to occur in Bako National Park.A complete and long term study covering other areas not included in this study would definitely increase bats diversity found in this park.